Quality Assurance Improvements in Australian University Libraries - Tang, Karen (2012)
Purpose: The purpose of this paper is to examine the growth in quality assurance maturity within the six Australian and New Zealand university libraries which make up the Libraries of the Australian Technology Network (LATN). Design/methodology/approach: The paper is based on benchmarking surveys of library quality assurance commissioned by LATN in 2005/2006, with a follow up study in 2010. The author led the conduct and analysis of both surveys. The 2005/2006 study reviewed quality assurance practices at the member libraries, to draw out examples of best practice and identify gaps and possible areas for improvement within the libraries. It was based on a review of member libraries’ websites, a questionnaire completed by a nominee from each member library, and follow up in person interviews with each nominee and the University Librarian of each institution. In 2009/2010 the same questionnaire was re-administered to investigate whether changes had occurred in the intervening period, including what improvements had been made and where there were still gaps. Had the conduct of quality audits by the Australian Universities Quality Agency had an impact? Had members made improvements to their quality assurance processes based on the findings of the first study or for other reasons? To elicit additional information, follow up interviews are being carried out in 2011. Findings: In 2005/2006 the reviewers found three models of responsibility for quality assurance: centralised, within a manager's portfolio and devolved. Each was appropriate to a different level of quality maturity, with a centralised model considered to be most appropriate at the early stages of development. Whereas in 2005/2006 only one library had a centralised model, by 2010 three libraries had adopted this model and one had moved on from it.The paper compares applications of these models in the libraries and looks at the extent to which growth in quality assurance in the libraries is associated with adoption of the centralised model. It distinguishes the formal creation and appointment of a quality officer position from the ad hoc individual efforts in quality which can and do occur in many libraries. In 2005/2006 only two libraries had a functioning and well-maintained quality framework which the LATN reviewers considered to be a hallmark of best practice in quality assurance. By 2010 this number had doubled to four. The paper looks at the quality, planning and/or performance frameworks in place and whether they were selected or developed by the library or imposed by their parent university. The impact of the adoption of a framework on the development of quality policies, procedures and documentation to achieve comprehensiveness, standardisation and repeatability in quality assurance are considered. A notable change between the 2005/2006 and the 2010 surveys was the growth in individual work planning and performance review, which was identified by the LATN reviewers as a sector-wide gap in 2005/2006. Ideally, use of such plans and assessments should assist in the taking quality beyond library management, to develop amongst the library staff a culture of continuous improvement. Originality/value: The paper provides real examples of how quality assurance can and has been improved in libraries, within a five year timeframe. While it is based on the experience of Australian and New Zealand libraries, it addresses concerns and provides solutions which are appropriate internationally. It provides a range of options which an individual library could adopt depending on its own context.